Let's go with Labour for the new Britain : the Labour Party's manifesto for the 1964 general election. - Labour Party (London : Labour Party, 1964)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Labour Party; parlementsverkiezingen; Groot-Brittannië.